Marketing for the mental health professional : an innovative guide for practitioners - Diana, David P. (Hoboken, N.J. : Wiley, 2010)
'There are a few available training programs on the practical aspects of succeeding in the mental health profession for mental health professionals. Marketing for the Mental Health Professional provides powerful, proven sales and marketing techniques as well as strategies to achieve high quality, value-based services in the mental health practice. Filled with real-life stories and helpful tips, this book presents tools for generating better publicity, conducting a job search, understanding the value propositions, and engaging with clients for long-term success for both new and seasoned practitioners.'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Mental health services -- Marketing; Mental Health Services -- organization & administration; Achievement; Marketing of Health Services; Professional-Patient Relations